Porous silicon film overcoating biomass char-supported catalysts for improved activity and stability in biomass pyrolysis tar decomposition. Issue 17 (2nd August 2021) - Liang, Shuang; Tian, Beile; Guo, Feiqiang; Dong, Yichen; Du, Shilin; Qian, Lin
Abstract : A C-SiO2 core–shell structure catalyst was prepared via a two-step pyrolysis method, and the support effect and reaction mechanism were discussed for this novel system. Abstract : In this work, porous silicon film overcoating biomass char-supported catalysts were synthesized, and biomass pyrolysis tar decomposition reactions were evaluated. With the presence of Ni and Fe (SC@Ni1 Fe1 @SiO2 ), high-density and well-dispersed Ni nanoparticles (NPs) and face-centered cubic FeNi3 NPs were formed on the char surface as catalytic active sites, and a silicon-based mesoporous film was formed and overcoated on the char-supported catalysts. The overcoating SiO2 film combines with the microporous biochar, forming a hierarchical structure that enhanced the adsorption of the tar molecules and gases, and prolonged the reaction time. FeNi3 alloy nanoparticles with a small particle size of 2 nm were formed and penetrate the SiO2 film, which prevented the metal nanoparticles from aggregation and reduces the probability of carbon deposition. At a relatively low temperature of 600 °C, a high tar conversion efficiency of 92.38% was obtained using SC@Ni1 Fe1 @SiO2 as the catalyst, leading to a significant increase in the fuel gas yield. After five times consecutive reuse under the same conditions, tar conversion efficiency and the gas yield were almost unchanged. The char-SiO2 core–shell structure of the catalyst is well maintained, and carbon deposition occurs on the silicon-based protective film to protect the catalyst from deactivation.